Treatment of Recurrent Urinary Tract Infection Symptoms with Urinary Antiseptics Containing Methenamine and Methylene Blue: Analysis of Etiology and Treatment Outcomes - Gama CRB; Pombo MAG; Nunes CP; Gama GF; Mezitis SGE; Suchmacher Neto M; Guimarães OR; Geller M; Oliveira L; de Souza da Fonseca A; Sitnoveter A; Goldwasser G; et al. (Research and Reports in Urology, 2020)
Carlos Romualdo Barbosa Gama,1 Manoel Antônio Gonçalves Pombo,1 Carlos Pereira Nunes,1 Gustavo Falcão Gama,1 Spyros GE Mezitis,2 Mendel Suchmacher Neto,3 Oscar Roberto Guimarães,1 Mauro Geller,1,4 Lisa Oliveira,4 Adenilson de Souza da Fonseca,1 Aline Sitnoveter,1 Gerson Goldwasser,3 Karin Soares Cunha,5 Luiz Guilherme Darrigo Junior6 1UNIFESO Medical School, Rio de Janeiro, Brazil; 2New York-Presbyterian Hospital/Weill-Cornell Medical Center, New York, NY, USA; 3Santa Casa de Misericórdia do Rio de Janeiro, Rio de Janeiro, Brazil; 4Universidade Federal do Rio de Janeiro (UFRJ), Rio de Janeiro, Brazil; 5Pathology Department, Faculdade de Medicina - Universidade Federal Fluminense (UFF), Niterói, Brazil; 6Ribeirão Preto Medical School, University of São Paulo, Ribeirão Preto, BrazilCorrespondence: Mauro Geller Av. Ataulfo de Paiva, 135 sl. 1104, Rio de Janeiro, RJ 22440-901, BrazilTel +55 21 3875-6660Fax + 55 21 2259-3395Email maurogeller@gmail.comPurpose: Urinary antiseptics including methenamine and methylene blue are used in the symptomatic treatment of urinary tract infections (UTIs).Patients and Methods: This was a prospective, double-blind, randomized, double-dummy safety and efficacy study of 2 urinary antiseptic combinations in the symptomatic treatment of recurrent cystitis: methenamine 120mg + methylene blue 20mg (Group A) versus acriflavine 15mg + methenamine 250mg + methylene blue 20mg + Atropa belladonna L. 15mg (Group B). All subjects underwent pretreatment urine culture and antibiotic sensitivity tests prior to 3-day oral treatment with study drug, followed by 3 days of antibiotic therapy (based on urine culture) + study drug treatment. Efficacy was evaluated using the Urinary Tract Infection Symptoms Assessment Questionnaire (UTISA). The primary endpoint was the percentage of patients presenting improvement in cystitis manifestations on the UTISA domain “Urination Regularity” at Visit 2. The primary safety variable was the incidence of treatment-related adverse events.Results: A total of 144 subjects were randomized per group and 272 completed the study. Primary endpoint analysis demonstrates homogeneity between treatment groups, with 69.4% and 72.2% subjects, respectively, showing improvement in the score of the urinary regularity UTISA domain after 3 days of treatment (p= 0.87). At Visit 2, incidence of treatment-related adverse events was higher in Group B (Group A: n= 11, Group B: n= 31, p= 0.0057).Conclusion: Both treatments were effective in reducing UTI symptoms assessed by UTISA questionnaire after 3 days of treatment. The two regimens were comparable in incidence of adverse events, but the combination of methenamine + methylene blue resulted in fewer treatment-related adverse effects.Keywords: urinary tract infection; UTI, urinary antiseptics, UTISA, methenamine, methylene blue